Assessing seismic response equivalency for fixed pile-founded offshore platforms utilizing PSDA and IDA. (November 2022) - Babaei, Samira; Amirabadi, R.
Abstract: Detrimental seismic effects on offshore platforms safety and serviceability highlight the necessity of these infrastructures fundamental seismic investigations that contribute to the design and maintenance of reliable structures. To this end, probabilistic seismic response evaluation of fixed pile-founded offshore platforms utilizing probabilistic seismic demand analysis (PSDA) has been employed. Housner Intensity-Drift Ratio as the derived optimal pair -in which engineering demand parameters (EDPs) are calculated, given the ground motion intensity measures (IMs)- is chosen. A selection of optimal IM–EDP pairs is made based on the criteria of practicality, effectiveness, efficiency and sufficiency. In this study, equivalency of the results is evaluated comparing the same IM-EDP pairs against the method of incremental dynamic analysis (IDA). Furthermore, another objective of this assessment is to investigate the appropriate number of required ground motion records according to which structural seismic responses are not over/underestimated. The uncertainties associated with fixed pile-founded offshore platform brace configurations, besides the effect of soil-pile-structure interaction (SPSI) are thoroughly considered, generating more accurate and vigorous results. The findings of this study demonstrate that seismic responses resulted from IDA approach utilizing 12 ground motion records scaled 7 times matches well with those derived from PSDA.